The Disability Tax Credit: Why it Fails and How to Fix It - Wayne Simpson; Harvey Stevens (The School of Public Policy Publications, 2016)
When the government establishes a social program whose primary purpose is to help provide support to low-income people with disabilities, its success should be measured on how well it achieves that purpose. Unfortunately, there are reasons to seriously question the usefulness of Canada’s disability tax credit since it is helping so very few of the people it is intended to support. In fact, the credit is helping only a small number of Canadians with disability who qualify for it, and least of all those in the poorest families who receive an average of only $29 annually. The reason is not hard to see: Designing the support as a tax credit means that only those Canadians with disability who earn enough income to have them owing taxes can take advantage of it. Yet it is an unfortunate reality that people with disability are often at low incomes precisely because their disability leaves them unable to work in full-time, wellpaid jobs. Thus, the very people who need this support most are the ones least able to take advantage of it. In other words, the neediest disabled Canadians are receiving the least benefit. Far from being a successful policy, the results of the disability tax credit can only be described as disappointing. There is an uncomplicated way to begin rectifying this: By making the disability tax credit refundable. Along the same lines as a guaranteed minimum income, or negative income tax, those low-income Canadians with disabilities who qualify for the credit but lack sufficient income to benefit from the credit could simply be made eligible for a refund of the amount they cannot claim. Simply doing that, turning this non-refundable credit into a refundable credit, would increase the average benefit for Canada’s poorest families with a disabled person from $29 to $511, increasing their total income by a meaningful 4.1 per cent. Just as importantly, where a meagre 0.2 per cent of these families now get any benefit at all from the credit, a refundable credit would now see a majority, 56.4 per cent, receiving benefits. We estimate that this would mean added costs to the federal program of a modest $72 million, or a 17 per cent increase. A similar reform at the provincial level would cost an additional $31 million. An even more effective option for ensuring better outcomes for this policy, however, would be to both make the tax credit refundable and enhance it to triple its value. This would ensure that virtually every family with a disabled person below the low income cut-off, would benefit from the credit and this enhancement would raise their incomes a far more consequential 27 per cent. The costs of this enhanced refundable disability tax credit would be, of course, notably higher, estimated at $516 million federally and $240 million provincially, but it would actually achieve the outcomes that this policy ostensibly intends. The current program may be cheaper, but the value it delivers is trifling and the money, therefore, is arguably heavily wasted. For years there have been calls to make this tax credit work better through refundability. We now have evidence that an enhanced refundable disability tax credit would make the significant difference in the lives of lowincome Canadians with disabilities that the policy was designed to do, but has so far largely failed to do.